A worthy pursuit - Witemeyer, Karen (Bethany House, a division of Baker Publishing Group, 2015)
"In 1891 Texas, teacher Charlotte Atherton is on the run to keep a little girl entrusted to her care safe, while tracker Stone Hammond is in close pursuit--until he learns the truth of the situation and discovers his heart may have a new pursuit"--